Meta-Analysis on the Neutrophil-Lymphocyte Ratio in Rectal Cancer Treated With Preoperative Chemoradiotherapy: Prognostic Value of Pre- and Post-Chemoradiotherapy Neutrophil-Lymphocyte Ratio - Lee, Soo Jin; Kim, Kyubo; Park, Hae Jin (Frontiers in Oncology, 2022)
Background To evaluate the prognostic value of neutrophil-lymphocyte ratio (NLR) in rectal cancer patients treated with preoperative chemoradiotherapy (CRT) and curative surgery. Methods A comprehensive search of the EMBASE and PubMed databases was performed to screen studies that compared treatment outcomes according to the pre-CRT and/or post-CRT NLR in patients receiving preoperative CRT and curative surgery for locally advanced rectal cancer. Hazard ratios (HRs) for disease-free survival (DFS) and/or overall survival (OS) were extracted, and a random-effects model was used for pooled analysis. Results Totally, 22 retrospective studies comprising 6316 patients were included. Preoperative CRT was administered with concurrent chemotherapy (mostly fluoropyrimidine-based regimens). The elevated pre-CRT NLR was significantly associated with an increased risk of recurrence (HR, 1.54; 95% confidence interval [CI], 1.31-1.81) and death (HR, 2.14; 95% CI, 1.61-2.84). Post-CRT NLR was reported in only 3 of 22 studies, and the correlation was not statistically significant for recurrence (HR, 1.44; 95% CI, 0.86-2.41) or death (HR, 2.38; 95% CI, 0.94-6.07). Conclusions Elevated pre-CRT NRL, but not post-CRT NRL, is associated with inferior DFS and OS. Further studies are needed to confirm the prognostic value of NLR in rectal cancer patients receiving preoperative CRT.